Efektifitas Konsumsi Susu Kedelai Dan Senam Aerobic Untuk Mengatasi Keluhan Hot Flushes - Titah Khisni Hayati; Salfia Darmi; Lina Nurul Izza; Tri Widiyanti, Elliana; Yuni Antika; Tanti Maryani; Ria Magdalena Damanik; Sri Mutmainah (2025)
Perimenopause is a transitional phase between premenopause and postmenopause. One of the main symptoms of menopause syndrome is the occurrence of hot flushes. Hot flashes are common in women almost all over the world, where the prevalence is around 70-80% in European women, in Malaysia around 57%, China 18% and 10% -20% of women in Japan and Indonesia. One way to reduce the incidence of hot flushes is to provide soy milk and aerobic exercise.To determine the effectiveness of soy milk consumption and aerobic exercise to overcome hot flushes in perimenopausal women.This type of research is a qualitative research with a study case literature approach. The sample used in this study was 6 people who experienced hot flushes. To measure hot flushes in perimenopausal women using the HFRS (Hot flushes Range Scale) questionnaire. The research location was at the Pasir Putih Depok Health Center UPTD, conducted for 2 weeks.In the Aerobic exercise group before the intervention, the degree of hot flushes was 9 with a moderate category, after the intervention decreased to a score of 1, meaning no hot flushes occurred. While in soy milk before the intervention, the degree of hot flushes was 9 with a moderate category, after the intervention decreased to a score of 2, meaning mild hot flushes occurred.Aerobic exercise is more effective in reducing hot flushes complaints in perimenopausal women than soy milk. It is expected to be used as an intervention to reduce the incidence of hot flushes in perimenopausal women.